Maximization Problems for Second Order Elliptic Equations (Contemporary Mathematics, 2021)
We investigate the maxima in classes of rearrangements of some functionals associated with solutions to Dirichlet problems for second order elliptic equations.
Keywords: rearrangements, second order elliptic equations, maximization problems